Efektifitas Perbandingan Buerger Allen Exercise dan Senam Kaki terhadap Nilai ABI pada Penderita DM Tipe II (Journal of Telenursing (JOTING), 2019)
The purpose of this study is to obtain a comparison of the effectiveness of the Buerger Allen Exercise and foot exercises on the value of the Ankle Brachial Index (ABI) in patients with Type II Diabetes Mellitus. This research method is a quantitative method with a research design Quasi Experiment pre and post test two groups. The results showed that there was a significant difference in the value of the Ankle Brachial Index (ABI) before and after being given Buerger Allen Exercise and foot exercises, namely p